1996
DOI: 10.1007/bf01326035
|View full text |Cite
|
Sign up to set email alerts
|

A new formula for the volume of lattice polyhedra

Abstract: Abstract. Let L, be the lattice consisting of all points x in R N such that nx belongs to the fundamentallattice L 1 of points with integer coordinates. When the vertices of a polyhedron P in R N are restricted to lie in L 1 there is a formula which relates the volume of P to the numbers of points of L1 .... , Lr~ in the interior and on the boundary of P. The aim of this note is to show that the volume of P can be determined only by means of the numbers of points of L1,..., L N lying in the interior of P and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…It can be obtained by using formula (3) (2) and (3) applicable to proper lattice polyhedra in R N established by Macdonald [6]. We refer the reader also to [3] and [5]. Note that in [5] it is shown that the volume of a proper lattice polyhedron P in R N can be determined by means only of the numbers of points from L1 ,..., LN lying in the interior of P.…”
Section: Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be obtained by using formula (3) (2) and (3) applicable to proper lattice polyhedra in R N established by Macdonald [6]. We refer the reader also to [3] and [5]. Note that in [5] it is shown that the volume of a proper lattice polyhedron P in R N can be determined by means only of the numbers of points from L1 ,..., LN lying in the interior of P.…”
Section: Remarksmentioning
confidence: 99%
“…We refer the reader also to [3] and [5]. Note that in [5] it is shown that the volume of a proper lattice polyhedron P in R N can be determined by means only of the numbers of points from L1 ,..., LN lying in the interior of P.…”
Section: Remarksmentioning
confidence: 99%